Unfenced Borders Cause Differences in Vegetation and Fauna Between Protected and Unprotected Areas in a Tropical Savanna - Nyamukuru, Antonia; Grytnes, John-Arvid; Tabuti, John R. S.; Totland, Ørjan (Tropical Conservation Science, 2019)
Protected areas generally occur within a matrix of intensively human-modified landscapes. As a way to maintain the biodiversity in these areas, enclosure by fencing is often preferred. This strategy, however, is costly and little is known about the effectiveness of the alternative of unfenced borders on the vegetation and fauna. The objectives of this study are to assess whether there is a distinct difference in biodiversity and composition of plants and mammals between the protected Lake Mburo National Park and the adjacent ranchlands across an unfenced border and to determine the associations between vegetation and faunal species over the same border. We recorded herbaceous vegetation, woody vegetation, and mammal species composition in plots 300 to 500m away from the border both inside the protected area and in the adjacent ranchlands. The species composition of herbs and mammals in the protected area differ from the adjacent ranchlands, but there is no difference for trees and shrubs. After accounting for land-use type, distance from the border did not significantly account for any additional variation. We also find a correlation between the species composition of vegetation and fauna. Our results suggest that unfenced borders around protected areas create a clear effect.
Keywords: Border; Disturbance; Fauna; Herbaceous vegetation; Plant-herbivore interaction; Protected area; Ranchlands; Savanna